Unified Test of Causality and Cost of Carry Model : Pricing of the Kuala Lumpur Composite Index Futures Contract - Lau, Kenny Yee Sheng (2011)
This paper examines the causal relationship and the validity of the cost of carry model for pricing the FBMKLCI futures contracts. The test is carried out over the time period of 3/1/2006 – 30/6/2011 where it is split into two sub periods based on the changes in the index constituents and refresh times. The empirical work is carried out using the economic modelling based on the VECM framework for spot and futures prices. Our findings show that there is some (but weak) evidence against the cost of carry relationship between spot and futures prices in both our sub periods. This research also found bidirectional causality between spot and futures prices with a stronger causality from futures to spot. Strong mean reversion was found in the returns of both spot and futures returns suggesting overreaction in spot and futures price to new information.